Increasing seasonal influenza vaccination uptake using community pharmacies: experience from the Isle of Wight, England. (15th April 2013) - Warner, John Gary; Portlock, Jane; Smith, Jenifer; Rutter, Paul
Abstract: Objective: Influenza vaccination rates achieved by general medical practice on the Isle of Wight, England, have been consistently lower than regional and national averages despite practices pursuing an active programme of patient engagement. The objective of this work was to determine whether inclusion of community pharmacies in an influenza vaccination programme improves vaccination rates and is acceptable to patients. Methods: The Isle of Wight Primary Care Trust commissioned a community pharmacy seasonal influenza vaccination service to augment that offered by general medical practice. Vaccination rates were monitored as well as determining patient perception of a pharmacy‐based service by self‐administered survey. Key findings: Eighteen community pharmacies vaccinated 2837 patients and accounted for 9.7% of all patients vaccinated on the island. The pharmacy service contributed to improved patient vaccination rates in both the over‐ and under‐65 age groups and increased the number of patients receiving a vaccination for the first time. Pharmacies vaccinated proportionately more carers and frontline healthcare workers than medical practices. Patient satisfaction with the pharmacy‐based service was high, with access seen as a major advantage over general medical practice. The pharmacy‐based service also vaccinated patients that ordinarily would not have accessed medical services. Conclusions: Involvement of community pharmacies in the seasonal influenza vaccination programme can help increase vaccination rates and is associated with high levels of patient acceptability.